2023
DOI: 10.1186/s40364-023-00494-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based radiomic prognostic signature for locally advanced oral cavity squamous cell carcinoma: development, testing and comparison with genomic prognostic signatures

Abstract: Background . At present, the prognostic prediction in advanced oral cavity squamous cell carcinoma (OCSCC) is based on the tumor-node-metastasis (TNM) staging system, and the most used imaging modality in these patients is magnetic resonance image (MRI). With the aim to improve the prediction, we developed an MRI-based radiomic signature as a prognostic marker for overall survival (OS) in OCSCC patients and compared it with published gene expression signatures for prognosis of OS in head and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…From the literature survey, 7 reproducible MRI-based radiomic signatures for HNSCC patients were identified 18 , 19 , 29 33 as those which satisfy the minimum requirements for reproducibility. They are reported in Table 2 , along with their constitutive features in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the literature survey, 7 reproducible MRI-based radiomic signatures for HNSCC patients were identified 18 , 19 , 29 33 as those which satisfy the minimum requirements for reproducibility. They are reported in Table 2 , along with their constitutive features in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“… Ref. Image pre-processing Features Feature normalization Signature threshold R1 Bos 2021 29 (iii); (iv); (v) 10 (T1wCont) Z-score (no details) NA R2 Chen 2022 30 NA 6 (T1wCont) NA NA R3 Alfieri 2022 31 (i); (ii); (iii); (iv); (v) 3 (T1w, T1wCont, T2w) Z-score (µ and σ provided) NA R4 Siow 2022 32 (ii); (iii); (iv); (v) 4 (T1wCont) NA 0.5 R5 Mossinelli 2023 33 NA 2 (T2w) Unspecified standardization NA R6 Bologna 2023 19 (i); (ii); (iii); (iv); (v) 4 (T1w, T2w) Z-score (µ and σ provided) NA R7 Corti 2023 18 (iii); (iv); (v) 5 (T2w) Z-score (µ and σ provided) 0.082 (i) denoising, through a 3D Gaussian filter with a 3 × 3x3 voxel kernel and σ = 0.5; (ii) intensity non-uniformities correction, through the N4ITK algorithm; (iii) intensity standardization, using Z-score; (iv) voxel size resampling to a specific isotropic resolution, through B-spline interpolation, and (v) fixed-bin histogram discretization, with a specific number of bins. µ: media value for Z-score standardization σ: standard deviation for Z-score sta...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations also hint at the potential role of PET imaging in identifying cancer-associated genetic mutations 30 and the prospective use of radiomics-based imaging biomarkers for outcome predictions in head and neck cancer 31 . To the best of our knowledge, only a few studies 32 35 have identified MRI radiomics features that could be exploited as prognostic tools for overall survival in OSCC. Study 36 found a significant association between Rad-score (linear combination of three PET-based radiomics features) and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can extract many quantitative non-invasive tumor biomarkers with important potential implication for precision medicine across different cancer types including OTSCC [16] , [17] , [18] . Intra-tumor heterogeneity can be captured by first-order and higher-order textural features and may reflect the microstructural tissue characteristics and help clinicians to better stratify patients [19] .…”
Section: Introductionmentioning
confidence: 99%